2017
DOI: 10.1293/tox.2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of patchy thickening and reddish discoloration of active hair growth areas in the skin of New Zealand White rabbits

Abstract: Patchy thickening and reddish discoloration of active hair growth areas of skin in rabbits are occasionally found, and this gross feature could affect precise evaluation when conducting a dermal irritation test. Since little is known about the mechanism of this phenomenon, we examined the dorsal skin of New Zealand White rabbits morphologically and immunohistochemically in order to identify the possible mechanism responsible for developing these skin changes in relation to the hair cycle. Skin samples from 4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…During the anagen phase, hair follicles grow rapidly by cell proliferation and reach their longest length. After regression by apoptosis in the catagen phase, they enter the telogen phase [10, 11]. Apoptosis is a critical event in the regulation of the hair cycle as anagen hairs normally grow for 4–7 years in humans before the cycle enters into the resting phases of catagen and telogen [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…During the anagen phase, hair follicles grow rapidly by cell proliferation and reach their longest length. After regression by apoptosis in the catagen phase, they enter the telogen phase [10, 11]. Apoptosis is a critical event in the regulation of the hair cycle as anagen hairs normally grow for 4–7 years in humans before the cycle enters into the resting phases of catagen and telogen [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits are highly sensitive to skin irritation and are easy to feed in the laboratory. Thus, rabbits are widely used in skin penetration studies to predict human skin irritation and determine the safety 30. The results of the skin irritation study listed in Table 1 indicated that the skin of New Zealand rabbits were not allergic to the Tβ-4 ethosomal gel, Tβ-4 gel, and the blank gel after 24 h of application and 7 days of repeated applications.…”
Section: Resultsmentioning
confidence: 99%
“…Dogs differ from these categories, although hair loss associated with hair cycle arrest is seen 33 , 36 , 37 . Irregular hair spots in rabbits have been reported to appear as raised, thickened islands compared to the surrounding skin 38 . Therefore, attention should be paid to studies that evaluate skin reactions in rabbits.…”
Section: Cutaneous Adnexamentioning
confidence: 99%